Developing Students' Life Skills Through Entrepreneurship and Agropreneurship Education at Al-Itqan Islamic Boarding School, Depok - Rahman, Syaifur; Muarofah, Ulfiatul; Sodiq, Akhmad; Suparto, Suparto; Suwendi, Suwendi (Universitas Negeri Padang, 2024)
This study aims to examine the entrepreneurship and agropreneurship education programs that are optimally implemented at Al-Itqan Islamic Boarding School in developing students' life skills. Through a qualitative approach, this study highlights several aspects that influence the successful implementation of the program, including the concept that combines salaf pesantren education with entrepreneurship education with the aim of being an education, teaching, and development of entrepreneurial potential so that students have a combination of religiosity and entrepreneurial mentality so that they are capable of becoming an entrepreneur by conducting skills training and managing Islamic boarding school business units with all students such as agriculture, fisheries, animal husbandry, sewing, aqiqah catering, and agropreneurship, plantations, fisheries, animal husbandry , sewing, aqiqah catering, and culinary as well as a gradual and integrated guidance system through various activities such as entrepreneurship workshops (entrepreneurship seminars), direct practice in the field, special mentoring, and Al-Itqan study tours. With this program, the pesantren succeeded in developing the life skills of santri which include vocational skills or entrepreneurial skills theoretically and practically, santri are able to manage businesses so that they become tenacious and responsible individuals. In addition, the Islamic boarding school can also develop the economy of the boarding school independently in supporting the daily needs of students. Keywords: Education, Entrepreneurship, Agropreneurship, Life Skills, Al-Itqan Islamic Boarding School Depok.